Tert-butylamidinate tin(II) complexes: high activity, single-site initiators for the controlled production of polylactide - Nimitsiriwat,N; Gibson,VC; Marshall,EL; White,AJP; Dale,SH; Elsegood,MRJ (Dalton Transactions, 2007)
The tin(II) coordination chemistry of two monoanionic N,N-bis(2,6-diisopropylphenyl)alkylamidinate ligands is described. Complexation studies with the acetamidinate, [MeC(NAr)2]–, (Ar = 2,6-iPr2C6H3) are complicated by the side formation of the bis(amidinate) tin(II) compound, [MeC(NAr)2]2Sn, 1. By contrast, the bulkier tert-butylamidinate, [tBuC(NAr)2]–, allows tin(II) mono-halide, -alkoxide and -amide complexes to be isolated cleanly in high yields. Thus, the reaction of [tBuC(NAr)2]H with nBuLi and subsequent treatment with SnCl2 generates [tBuC(NAr)2]SnCl, 2, in ca. 70% yield. Reactions of 2 with LiOiPr, LiNMe2 and LiNTMS2 afford [tBuC(NAr)2]Sn(OiPr), 3, [tBuC(NAr)2]Sn(NMe2), 4, and [tBuC(NAr)2]Sn(NTMS2), 5, respectively. The molecular structures of complexes 1–4 are reported. Complexes 3, 4 and 5 have been investigated as initiators for the ring-opening polymerisation of rac-lactide: 3 and 4 display characteristics of well-controlled polymerisation initiators, but high molecular weight polymer is observed with 5 due to inefficient initiation, a consequence of the steric bulk of the NTMS2 unit. Polymerisations with 3 and 4 are faster than for the corresponding -diketiminate tin(II) complexes, consistent with the more open nature of the tin(II) coordination sphere.